A Rare Case of Diabetic Papillopathy Presenting with Pseudo-Foster Kennsedy Syndrome - Ting, Xiao Wei; Abd Jalil, Nor Fadzillah; Muhammed, Julieana (IIUM Medical Journal Malaysia, 2023)
Pseudo-Foster Kennedy syndrome (PFKS) is defined as unilateral disc oedema with contralateral optic nerve pallor, in the absence of intracranial pathologies. Diabetic papillopathy is a rare ocular manifestation of diabetes mellitus (DM). We report a rare case of PFKS secondary to diabetic papillopathy in a young patient with type 2 DM who had poor glucose control. There was optic disc swelling over the right eye and optic disc pallor over the left eye. His visual field assessment showed right inferior field defect and general depression in the left. Optical coherence tomography retinal nerve fibre layer showed normal thickness over the right eye and generalized thinning over the left eye. Neuroimaging and other laboratory investigations were unremarkable. With good glycemic control, the optic disc swelling over the right eye resolved. Visual field defect remained the same but retinal nerve fiber layer showed thinning in areas where the edema had resolved.